Minimalne temperature - Ogrin, Matej (Geografski obzornik, 2006)
The Minimum Temperatures of Cold Air Pools Measurements in winter 2005/2006 confirmed our assumptions, that temperatures in the cold air pools are much lower than temperatures, measured within national observing network. In alpine cold air pool Mrzla Komna on Komna plateau in Slovenian Julian Alps (1592 m a.), on January 25, 2006 the lowest temperature ever measured in Slovenia was recorded.
Keywords: klimatogeografija; microclimate; mikroklima; zrak; temperatura; temperaturni obrat; Slovenia; Slovenija